## Algebra: A Combined Approach (4th Edition)

If $x = -1$, then: Equation (a). $-2x + 10 = 12$ Equation (b). $6x^{2} + 11x -20 =-25$
If $x = -1$, then: Equation (a). $-2x + 10$, then we need to substitute $x$ with $-1$. So, the equation becomes: $(-2)(-1) + 10$, so: = The first term is $-2$ multiplied by $-1$, and a negative number multiplied by another negative number is positive, so $-2$ multiplied by $-1$ = 2. = 2 + 10, then, is 12. = 12 (answer). Equation (b). $6x^{2} + 11x -20$, then we need to substitute $x$ with $-1$. So, the equation becomes: $6(-1)^{2} + (11)(-1) -20$. = The first term is $6$ multiplied by $1$ since (-1) multiplied by itself is multiplying one negative number with another negative number, which makes it positive. So $6$ multiplied by $1 = 6$. = The equation then becomes: $6 + (11)(-1) -20$ = The next order of operation based on PEMDAS (Parentheses, Exponents, Multiplication, Division, Addition, and Subtraction) further simplifies the equation to $6 -11 -20$. = As such, we want to solve left to right because of the remaining operations (Addition and Subtraction). So, the equation becomes: = $(6-11) -20$. = $6-11$ is $-5$. = The equation then looks like this: = $-5 -20$, which means the answer is -25.